The integration of body-mind-instrument in musical art: cognitive aspects and its significance according to the understanding of Brazilian musicians - Morgado, Elsa Maria (2019)
In this investigation, result of a doctoring thesis, we discuss the study of neuro-science in its respectic pertinente topics relating to musical art, linked to the body-mind-instrument integration. Our definition of the problem carried out a survey about the musicians 'understanding of the cognitive, motivational and emotional processes integrated in the body as well as the performance of the musical performance. According to our general objective, we evaluated the professionals' perceptions about the body's role in musical execution, determining the problem. We applied closed questionnaires using the Likert scale in parallel to the qualitative approach questionnaire whose evaluation used the Bardin method of content analysis. The general hypothesis was that in the perception of the musicians since their formation the idea that musical performance is optimized by body-mind-instrument integration is present. Once the ten hypotheses have been validated, it is confirmed that the cognitive aspects are important for the body-mind-instrument integration in musical art.